Interpreting Islam - Donnan, Hastings (London ; Thousand Oaks, Calif. : SAGE, 2002)
Surrounded by myths and stereotypes, Islam is one of the least understood religions in the West. Interpreting Islam provides a penetrating guide to the diversity and richness of contemporary knowledge about Islam and Muslim society in general.
Interpreting interpretations of Islam / Hastings Donnan and Martin Stokes -- Orientalism, or the politics of the text / Bryan S. Turner -- Researching the radical : the quest for a new perspective / Beverley Milton-Edwards -- Islam in the media / Malise Ruthven -- Interpreting Islam in American schools / Susan L. Douglass and Ross E. Dunn -- Ideological dimensions of Islam : a critical paradigm / Ilyas Ba-Yunus -- Kissing cousins : anthropologists on Islam / Charles Lindholm -- Islam and the sea : the causes of a failure / Xavier de Planhol -- Organized charity in the Arab-Islamic world : a view from the NGOs / Jonathan Benthall -- Silver sounds in the inner citadel? Reflections on musicology and Islam / Martin Stokes.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Master record variable field(s) change: 082
Keywords: Islam; Islamic countries -- Social life and customs; Islam; RELIGION -- Islam -- General; Islam; Manners and customs; Islamic countries; Islam; Electronic books